Effect of food limitation on energy metabolism and burrowing activity of an infaunal marine bivalve, Mya arenaria - Fouzia Haider; Stefan Timm; Torben Bruhns; Mizra Nusrat Noor; Inna M Sokolova (PANGAEA, 2020)
Benthic organisms, such as infaunal bivalve, can experience and withstand prolonged food limitation in the temperate shallow coastal area. These organisms withstand the long food limitation by adjusting physiological processes which might cause trade-off between maintenance and other functions (e.g. burrowing). We have investigated the effects of prolonged food limitation (42 days without added food) on the tissue energy content, metabolites, RNA to DNA ratio, and burrowing activity of a common bioturbator, Mya arenaria. Mya arenaria decrease their respiration by 80% over 15 days of food limitation, and increase the time required for one burial cycle by 30-50% after 22 days of food limitation. We noticed a preferential switch in the fuel usage for burrowing depending on the stage of food limitation. The tissue energy content and free amino acid concentration decreases as a result of food limitation, however, there is a seasonal pattern. Our study suggest, although M. arenaria can withstand prolonged food limitation by lowering their basal maintenance cost and switching their fuel usage, their ecological function (bioturbation) could still be negatively affected.